Hubungan Antara Panjang Tungkai dan Kecepatam Kontraksi Otot Tungkai dengan Daya Ledak Otot Tungkai pada Anggota UKM Bola Voli Universitas Hasanuddin - Hebat Maha Putera Nusantara; Irianto Irianto (CV. Publikasi Indonesia, 2025)
Nowadays, sport has become a human need, both entertainment and a hobby for people (Lukito & Fahmi, 2020). Most of the sports that Indonesian people are interested in are game-type sports, one of which is volleyball. Volleyball is one of the most popular sports, and has even been ranked as the sport with the second most fans in the world (Damayanti et al., 2022). In volleyball, basic physical components determine the quality of movement during the game (Asnaldi, 2020). In the game of volleyball, muscle explosive power is the most substantial basic physical component, so this is the background for this research. This research aims to determine the relationship between leg length and leg muscle contraction speed and leg muscle explosive power at Hasanuddin University Volleyball UKM. This research is a quantitative study with a model using a cross sectional approach, the sampling technique used purposive sampling and obtained 36 samples that met the inclusion criteria. The results of the correlation test using the Pearson test between the independent and dependent variables showed significance (>0.05). It can be concluded that there is no relationship between leg length and leg muscle contraction speed and leg muscle explosive power in members of Hasanuddin University Volleyball UKM.